(untitled) (Annals of Medical Research, 2024)
Aim: This study investigates impacts of the COVID-19 pandemic on psychiatric emergency department admissions in province of Trabzon. Materials and Methods: The analysis involved examining changes in patient demographics, psychiatric diagnoses, and overall admission numbers during the pandemic compared to the previous year. The study focuses on patients aged over 16, utilizing records from three major healthcare centers in Trabzon province. Data including psychiatric diagnoses from the periods of March 11 to June 1 in both 2019 and 2020 are examined. Psychiatric diagnoses are categorized according to the International Classification of Diseases (ICD-10) classification system. Results: The findings indicate a substantial (32.5%) decrease in psychiatric emergency department admissions during the pandemic. This reduction is observed across all three hospitals, with the most significant decline occurring in the hospital designated for pandemic cases. Both men and women showed decreased presentations, and there is a statistically significant increase in the median age of patients. While overall psychiatric diagnoses decreased, the proportions of specific diagnoses including anxiety disorder, schizophrenia, depressive disorder, and substance dependence, shoved increase during the study period. Conclusion: Contrary to expectations, the study reveals a noteworthy decline in psychiatric emergency department admissions amid the COVID-19 pandemic. Similar trends are reported internationally. The discussion highlights potential factors contributing to this decrease, such as fear of COVID-19 transmission in hospitals, the perception that hospitals prioritize COVID-19 cases, and the availability of alternative mental health services. Concerns are raised regarding the long-term psychological impact of the pandemic, emphasizing the need for ongoing research and identification of high-risk groups not accessing emergency clinics during this period. The study acknowledges limitations, including reliance on hospital records and the potential for misdiagnoses in emergency settings, urging cautious interpretation of the results.